Scientific Americans : the making of popular science and evolution in early-twentieth U.S. literature and culture - Bruni, John (Intersections in literature and science., 2014)
The book challenges narrow readings of evolution as 'social Darwinism' by looking at evolutionary theory through the interrelated perspectives of science, North American naturalist literature, and popular journalism.